Adversity Quotient and Problem-solving Skills in Advanced Algebra - Oliveros, Joey (JPAIR Multidisciplinary Research, 2014)
Problem-solving is a 21st century necessity, but the disconcerting results in the recent international assessment of problem-solving skills reveal an obvious failure to put this  into action in classrooms. The purpose of the study was to ascertain the adversity quotient and its relationship to the problem-solving skills of 76 fourth-year high school students. Specifically, the study intended to determine the students' adversity profile in terms of the dimensions of adversity quotient and level of problem-solving skills in terms of the cognitive processes and to ascertain which adversity quotient dimension would best predict the problem-solving skills. The researcher employed a descriptive-correlation method, utilized a questionnaire adapted from Stoltz's Adversity Response Profile and a constructed problem-solving test in Advanced Algebra, and used mean, Pearson r, and multiple regression in the analysis of data. The findings revealed that the adversity quotient profile of the students is moderate and the problem-solving skill of the students is satisfactory.The level of adversity quotient and problem-solving skills of the respondents were found to be significantly related, and reach is the most efficient predictor of one's problem-solving skills.
Keywords: Mathematics Education; adversity quotient; problem-solving skills; advanced algebra; descriptive-correlation design; Davao City; Philippines